Struktura izvlečkov s področja materialov in tehnologij - Jamar, Nina (Knjižnica, 2009)
We investigated the structure of abstracts in Slovenian and international journals in the fieldof materials and technology. The aim of the study was to analyze the adherence of the abstracts published in Materials and Technology (MIT) and Materials Science and Technology (MST) to two different instructions for the preparation of abstracts (scheme based on ISO 214:1976 and Spanring system). 25 abstracts from each journal were divided into sentences. We tried to place the sentences into one of the categories of the above mentioned schemes. The research was a part of the postgraduatestudy in the Department of Library and Information Science and Book Studies (Faculty of Arts, Ljubljana) in September and October 2008. There are no important differences between MIT and MST. Spanring system seems more appropriate for the field of materials and technology. The place and the time of the research should be added to abstracts and the Hu-bit category should be distributed into two parts: Hu-M (method) and Hu-R (results). The recommended Spanring system should be harmonized with authors, who publish in there serials and the effect of the instructions should be analyzed, too.
Keywords: serijske publikacije; Materiali in tehnologije (periodična publikacija); Materials Science and Technology (periodična publikacija); izvlečki; standardi; ISO standardi; navodila; dokumentalistika